Thimerosal and children’s neurodevelopmental disorders - Maya, Luis (2006)
The causal relation of thimerosal (ethylmercury), preservative in pediatric vaccines, and the increase of children’s neurodevelopmental disorders as a result of the increase in immunization schemes is determined. The scientific information on thimerosal and its influence on the child’s neurodevelopmental disorders is reviewed. Evidences found in epidemiological, ecological, biomolecular, toxicology, biosecurity, fetal toxicology and reproductive health studies signal the possible causal association of thimerosal exposition and neurodevelopmental disorders of the child. Such neurotoxicity occurs in infants and fetuses of vaccinated pregnant women, due to mercury cumulative doses. The various evidences imply thimerosal as the causal agent, aggravating or triggering neurodevelopmental disorders of the child. The mercury toxicity forced progressive thimerosal withdrawal. Unfortunately, there was a delay in demonstrating thimerosal negative impact. Currently vaccines without thimerosal are causing less incidence of children’s neurodevelopmental disorders.